The Trox-2 Hox/ParaHox gene of Trichoplax (Placozoa) marks an epithelial boundary. - Jakob, W; Sagasser, S; Dellaporta, S; Holland, P; Kuhn, K; Schierwater, B (2004)
Hox and ParaHox genes are implicated in axial patterning of cnidarians and bilaterians, and are thought to have originated by tandem duplication of a single "ProtoHox" gene followed by duplication of the resultant gene cluster. It is unclear what the ancestral role of Hox/ParaHox genes was before the divergence of Cnidaria and Bilateria, or what roles the postulated ProtoHox gene(s) played. Here we describe the full coding region, spatial expression and function of Trox-2, the single Hox/ParaHox-type gene identified in Trichoplax adhaerens (phylum Placozoa) and either a candidate ProtoHox or a ParaHox gene. Trox-2 is expressed in a ring around the periphery of Trichoplax, in small cells located between the outer margins of the upper and lower epithelial cell layers. Inhibition of Trox-2 function, either by uptake of morpholino antisense oligonucleotides or by RNA interference, causes complete cessation of growth and binary fission. We speculate that Trox-2 functions within a hitherto unrecognized population of possibly multipotential peripheral stem cells that contribute to differentiated cells at the epithelial boundary of Trichoplax.